Enhancement of thermostable lipase production by a genotypically identified extremophilic Bacillus subtilis NS 8 in a continuous bioreactor. - Olusesan, Akanbi Taiwo; L. Kamaruzaman, Azura; Abu Bakar, Fatimah; Mohammed, Abdulkarim Sabo; Radu, Son; Abd. Manap, Mohd. Yazid; Saari, Nazamid (Karger, 2011)
Bacillus strain NS 8, a lipase-producing bacterium isolated from a Malaysian hot spring, is able to tolerate a broad range of temperature and pH, which makes it beneficial for this study. It generated PCR products with molecular weight of 1,532 bp, and the 16S rRNA sequence analysis identified it as Bacillus subtilis with accession number AB110598. It showed a 71% similarity index with B. subtilis using Biolog Microstation System. Its lipase production was optimized using a shake flask system by changing the physical (agitation speed, pH and temperature) and nutritional (nitrogen, carbon and minerals) factors. The most suitable combination of the basal medium for lipase production was 2.5% olive oil (carbon), 1.5% peptone (nitrogen), 0.1% MgSO 4 (mineral) at an optimum temperature of 50°C, pH 7.5 and 150 rpm agitation, giving an enzyme yield of 4.23 U/ml. Statistical optimization using response surface methodology was carried out. An optimum lipase production of 5.67 U/ml was achieved when olive oil concentration of 3%, peptone 2%, MgSO 4·7H 2O 0.2% and an agitation rate of 200 rpm were combined. Lipase production was further carried out inside a 2-liter bioreactor, which yielded an enzyme activity of 14.5 U/ml after 15 h of incubation.